Comorbidity diseases in adults with diagnosed interstitial lung diseases among inhabitants of the Silesian voivodeship, Poland - Ewa Niewiadomska; Małgorzata Kowalska; Jan E. Zejda (Medycyna Pracy, 2016)
Background: Interstitial lung diseases form a group of chronic diseases associated with a significant worsening of the quality of life. Proper management of these diseases involves the recognition and treatment of comorbidities, so it implies high direct and indirect costs of therapy. The lack of epidemiological data on the total incidence of interstitial diseases in Poland, as well as of information on their increasing incidence in other European countries justify investigations into epidemiological situation in the Silesian voivodeship (the southern region of Poland). Material and Methods: In a descriptive study registered data provided by the National Health Found in 2006–2010 were used to assess the temporal variability of standardized incidence rates. A data set included interstitial lung diseases and comorbidities in adults aged ≥ 19 years, residents of the Silesian voivodeship. Results: In the period under study standardized incidence ratios for interstitial lung disease declined from 9.7/100 000 adult population to 7.8/100 000 adult population. The most prevalent comorbidities included cardio-vascular diseases, chronic and infectious respiratory diseases, metabolic diseases and musculoskeletal and connective tissue diseases. Comorbidities were found more frequently in older people ≥ 65 years, except for sarcoidosis, which was four times more prevalent in younger people (19–64 years) compared to older patients. The estimated costs of treatment of the analysed diseases reached more than 50 mln zlotys (12 mln dollars) per year. Conclusions: A small but systematic decrease in the value of the standardized incidence rate for interstitial lung disease has been shown within the range of 9.7–7.8/100 000 adult inhabitants. The most frequent comorbidities included cardiovascular or chronic and infectious respiratory diseases. The high cost of therapy of interstitial lung diseases was largely related to simultaneous treatment of comorbidities. Med Pr 2016;67(6):751–763